People's Republic of China-Hong Kong Special Administrative Region : Financial Sector Assessment Program-Technical Note-Implications of Fintech for the Regulation and Supervision of the Financial Sector. (IMF Staff Country Reports; Country Report ;, 2021)
he Hong Kong Special Administrative Region (HKSAR) is among the world's major fintech hubs, well positioned to develop fintech initiatives from its traditional strengths in financial services. Key factors enabling the HKSAR to emerge as a fintech hub include its presence as an international financial center, its free-flowing talent and capital, a highly developed information and technology communication (ITC) infrastructure, and its most unique trait, a geographical and strategic advantage by proximity to the market in Mainland China.